2022
DOI: 10.1007/s11756-022-01200-w
|View full text |Cite
|
Sign up to set email alerts
|

Effectivity of polyphenolic polysaccharide-proteins isolated from medicinal plants as potential cellular immune response modulators

Abstract: Traditional medicinal herbs as Echinacea purpurea and Erigeron canadensis are recommended as a complementary supplementation for the treatment of diseases associated with immunological inflammation (e.g. common cold, coughs, bronchitis, upper respiratory infections, immunodeficiencies). This pathologic conditions are accompanied by the wide range of malfunctions or imbalances of the immune system, thus there is increased necessity for search of novel immunomodulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Purified polysaccharide extracts from Echinacea enhanced macrophage chemotaxis, production of reactive oxygen intermediates, and inhibited fungal growth in vivo (Roesler et al, 1991). Additionally, they enhanced the production and secretion of TNF-α, IL-10, IL-6, IL-12, and IL-1β (Paulovičová et al, 2022;Roesler et al, 1991;Steinmüller et al, 1993). Flavonoids are well-known antioxidants found in Echinacea and are expected to have anti-inflammatory and immunomodulatory properties (Farhan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Purified polysaccharide extracts from Echinacea enhanced macrophage chemotaxis, production of reactive oxygen intermediates, and inhibited fungal growth in vivo (Roesler et al, 1991). Additionally, they enhanced the production and secretion of TNF-α, IL-10, IL-6, IL-12, and IL-1β (Paulovičová et al, 2022;Roesler et al, 1991;Steinmüller et al, 1993). Flavonoids are well-known antioxidants found in Echinacea and are expected to have anti-inflammatory and immunomodulatory properties (Farhan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, E. purpurea enhances immune function by increasing the quantity, functionality, and mobility of various immune cells, such as neutrophils, polymorphonuclear leukocytes, and natural killer (NK) cells, thereby augmenting innate immunity and exerting anti-inflammatory effects (Khattab et al, 2019;Paulovičová et al, 2022). For instance, E. purpurea root extract was found to enhance the immune system by reducing the frequency and function of regulatory T cells (Kim et al, 2012).…”
Section: Leavesmentioning
confidence: 99%
“…The E. purpurea has been recommended as a medicinal plant for the treatment of the common cold, cough, bronchitis and upper respiratory infections [ 53 ]. In vitro experiments with human macrophages found that fresh-pressed juice and dried juice from the aerial parts of E. purpurea stimulated the production of cytokines including IL-1, IL-10, and TNF-α [ 54 ].…”
Section: Most Commonly Used Medicinal Plants For the Treatment Of The...mentioning
confidence: 99%